استخدام التيتانيوم في الغرسات السنية ؟ - ابراهيم تركماني; حسان حامد (Tishreen University, 2019)
منذ القديم والإنسان يبحث عن بديل المناسب للأسنان فقد استخدم عظام الحيوان واستخدم المعادن وكان استخدام المعدن الأصفر الذي يقاوم التآكل بشكل ممتاز اختيار موفق في ذلك الزمان. لكن هل الذهب هو المعدن المناسب لكي يكون البديل عن الأسنان بالطبع لا, وذلك لعدة أسباب أساسية وهي اختلاف الذهب في العديد من خواصه الفيزيائية والكيميائية عن مادة الأسنان الطبيعية منها الوزن النوعي والناقلية الكهربائية والحرارية وقيمة التوازن الترموديناميكي أي الترتيب في السلسلة الغلفانية التي تعبر عن تآكل المعدن, لذلك كان لا بد من البحث عن المعدن البديل. ومع تطور العلم وخاصة فيما يخص علم المواد وتمكن الإنسان من تحضير معادن جديدة لم تكن معروفة في السابق تم تحضير التيتانيوم الذي وجد تطبيقات ناجحة في العديد من المجالات, ومنها في طب الأسنان. تم دراسة سرعة تآكل سبائك التيتانيوم في الوسط الفموي مقارنة مع الذهب والبلاتين والفولاذ غير قابل للصدأ فوجد أن سرعة تآكل سبائك التيتانيوم منخفضة جدا" تسمح باستخدامها, كذلك تم مقارنة الوزن النوعي للأسنان مع الوزن النوعي للمعادن المذكورة فكان التيتانيوم الأقرب لها, وكذلك الأقل سمية للإنسان مما يجعله حاليا" المعدن الأفضل استخداما" في التعويضات السنية.     For a long time man has been looking for the suitable substitute for teeth. So he used the bones of animals and metals. Gold, which resists corrosion was an excellent choice in the point. But is gold the suitable metal to replace teeth? Of course no. this is because gold is different from the material of natural teeth in its physical and chemical properties in terms of specific weigh, electric and thermic conductivity and potential value in galvanic series. Therefore it was necessary to find another metal. With the development of science, especially material science, man was able to prepare new metals which were not known before. Titanium has proved many good applications in various fields including dentistry. Titanium alloy corrosion has been studied in oral environment compared with gold, platinum and stainless steel. It has been found out that corrosion speed of titanium alloy was very low this permits its use in teeth implant. Besides when the specific weight of teeth was compared with the specific weight of the metals mentioned above, it was found out that titanium was the best substitute. It was least toxic for man this is what makes it the best metal for prosthodontics at present.